ANALISA KINERJA SIMPANG JL.GAJAH MADA DAN JL.SENTOT PRAWIRADIRJO AKIBAT BANGKITAN PERJALANAN MASJID ROUDHOTUL MUCHLISIN DENGAN METODE PKJI 2014 - Muhammadiyah Yoza Wildan Fahmi; Rofi Budi Hamduwibawa; Taufan Abadi (HEXAGON, 2021)
The intersection of Jl.Gajah Mada and Jl. Sentot Prawirodirjo is an intersection with 3 arms (East, South, West). Where to Jl.Gajah Mada is a national road, which consists of 2 lanes and 3 lanes. Meanwhile, Jl. Sentot Prawirodirjo is a local road which consists of 1 lane 2 lanes. Jl Gajah Mada is the center or area of shopping and offices .. On Jl. Gajah Mada has also built a shopping center and a new generation building, so that it will increase traffic flow in the area. One reason why traffic lights are needed is to make a U-turn too long before  this intersection. So it is necessary to analyze how the intersection performance before and after the traffic light. The analysis used is the Indonesian Road Capacity Guidelines method (PKJI 2014). This analysis includes the degree of saturation (DJ), delay, queue length. From the results of the calculation evaluation, the level of intersection service is better with the presence of traffic light, than before the traffic light. Likewise with the analysis of the awakening from the mosque, which did not have a significant effect on the intersection of Jl. Gajah Mada and Jl. Sentot Prawirodirjo.